PENGARUH KETERAMPILAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT. UNITED TRACTORS KOTA SORONG - Susetyowati Sofia; Agilistya Rahayu (Lampung Selatan: Sekolah Tinggi Ilmu Ekonomi Muhammadiyah Kalianda, 2022)
This study aims to see (1) the effect of skills on employee productivity at PT. United Tractors City of Sorong. (2) The influence of the work environment on the productivity of the employees of PT. United Tractors City of Sorong. (3) The influence of skills and work environment on employee productivity of PT. United Tractors City of Sorong. This research uses descriptive method and without using a quantitative approach. The population in this study were employees at PT. United Tractors City of Sorong. The sampling technique used purposive sampling with a sample size of 56 people. The data technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple regression.The results showed that: Skills have a positive effect on employee productivity at PT. United Tractors City of Sorong. This is evidenced by the t-count value of 5.949> t table of 2.00575 with a significant value of 0.000 <from the significance level of 0.05 and the regression coefficient having a positive value of 0.247. The work environment has a positive effect on the productivity of the employees of PT. United Tractors City of Sorong. This is evidenced by the t-count value of 8.935> t table of 2.00575 with a significant value of 0.000 <of a significance value of 0.05 and the regression coefficient having a positive value of 0.629. Skills and work environment have a positive effect simultaneously on the productivity of employees of PT. United Tractors City of Sorong. This is evidenced by the value of Fcount of 42.999> Ftable of 3.17 with a significant value of 0.000 <of a significance value of 0.05 and the regression coefficient having a positive value of 0.619. Keywords: , Work Environment, Employee Productivity.